Executive review of hydrostatic pressure effects on sludge pretreatment by sonication - Le, Ngoc Tuan; JULCOUR-LEBIGUE, Carine; DELMAS, Henri (Vietnam Journal of Science and Technology, 2016)
The effect of hydrostatic pressure on sludge disintegration was studied for the first time using pressurized nitrogen in different operating conditions: sludge types, specific energy input ES, power input PUS, probe size, temperature T, and frequency FS. Optimum pressures (> 1 bar) were found as a function of acoustic intensity due to an increase in both cavitation threshold and cavitation intensity when increasing hydrostatic pressure. Under convenient hydrostatic pressure, the effect of US intensity IUS on DDCOD was much higher than that at atmospheric pressure. The most effective isothermal sonication would be high PUS, low FS, convenient excess pressure, and adequate total solid concentration, i.e. 360 W (35 mm diameter probe), 12 kHz, 3.25 bar, and 28 gTS/L, respectively according to our equipment possibilities. Besides, positive effects of pressure associated with high power adiabatic US were also achieved. The major result was that the optimum pressure depends on PUS, IUS (or probe size), and T, but not on ES, FS, nor sludge type. In general, sludge disintegration efficacy was significantly improved by sonication at the optimum pressure, especially at low ES, leading to a potential of energy input savings in sludge sonication pretreatment, but also in most of ultrasound assisted processes.